Fusion-mediated chromosomal instability promotes aneuploidy patterns that resemble human tumors - Delespaul, Lucile; Merle, Candice; Lesluyes, Tom; Lagarde, Pauline; Le Guellec, Sophie; Pérot, Gaëlle; Baud, Jessica; Carlotti, Martina; Danet, Coralie; Fèvre, Murielle; Rousseau, Benoit; Durrieu, Stéphanie; et al. (Oncogene, 2019)
Oncogenesis is considered to result from chromosomal instability, in addition to oncogene and tumor-suppressor alterations. Intermediate to aneuploidy and chromosomal instability, genome doubling is a frequent event in tumor development but the mechanisms driving tetraploidization and its impact remain unexplored. Cell fusion, one of the pathways to tetraploidy, is a physiological process involved in mesenchymal cell differentiation. Besides simple genome doubling, cell fusion results in the merging of two different genomes that can be destabilized upon proliferation. By testing whether cell fusion is involved in mesenchymal oncogenesis, we provide evidence that it induces genomic instability and mediates tumor initiation. After a latency period, the tumor emerges with the cells most suited for its development. Furthermore, hybrid tumor genomes were stabilized after this selection process and were very close to those of human pleomorphic mesenchymal tumors. Thus genome restructuring triggered by cell fusion may account for the chromosomal instability involved in oncogenesis.